Methyl tert butyl ether (MTBE) is anti- angiogenic in both in vitro and in vivo mammalian model systems - Kozlosky, John (J Appl Toxicol, 2012)
Methyl-tertiary butyl ether (MTBE), a well known gasoline oxygenate, and FDA approved gallstone treatment, has been previously shown to specifically target teleost embryonic angiogenesis. The studies reported here were to determine if similar vascular disrupting effects occurred in higher vertebrate models. Rat brain endothelial cells were isolated and allowed to form microcapillary-like tubes on Matrigel. MTBE (0.34–34.0 mM) exposure resulted in a dose-dependent reduction of tube formation, with the LOAEL at 0.34 mM, while MTBE’s primary metabolite, tertiary butyl alcohol had no effect on tube formation. HUVECs, a primary cell line representing macrovascular cells, were able to form tubes on Matrigel in the presence of MTBE (1.25 – 80 mM), but the tubes were narrower than those formed in the absence of MTBE. In a mouse Matrigel plug implantation assay, 34.0 mM MTBE completely inhibited vessel invasion into plugs containing Endothelial Cell Growth Supplement (ECGS) compared to control plugs with ECGS alone. When timed-pregnant Fisher 344 rats were gavaged with MTBE (500–1500 mg/kg) from day 6 of organogenesis through 10 days post parturition, no organ toxicity or histological changes in pup vasculature were observed. Therefore, MTBE is anti-angiogenic at mM concentrations and therefore a potential use as an anti-angiogenic treatment for solid tumors with minimal toxicity.